2018
DOI: 10.4066/biomedicalresearch.64-18-549
|View full text |Cite
|
Sign up to set email alerts
|

Salvadora persica leaf aqueous extract attenuates hyperglycemia and hyperlipidemia in alloxan induced diabetic male rats

Abstract: Background: Herbal medicine has been widely used in controlling diabetes and obesity for avoiding their complications. Objectives: The anti-diabetic, antioxidant and anti-lipidemic activity of Salvadora persica leaf aqueous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the present study, the alloxan-induced diabetes in the hypercholesterolemic rats occurs via a series of correlated events in the pancreatic beta cells, started with the injury of beta cells by the accumulation of alloxan followed by generation ROS with its reduction product, dialuric acid and finally the autoxidation of the dialuric acid that generates superoxide radicals, hydrogen peroxide and hydroxyl radicals that lead to the death of these beta cells [12,27,44,45]. The pancreatic beta cells are characterized by their low antioxidative defence capacity that leads to their death and the insulin-dependent alloxan diabetes [44,45].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the present study, the alloxan-induced diabetes in the hypercholesterolemic rats occurs via a series of correlated events in the pancreatic beta cells, started with the injury of beta cells by the accumulation of alloxan followed by generation ROS with its reduction product, dialuric acid and finally the autoxidation of the dialuric acid that generates superoxide radicals, hydrogen peroxide and hydroxyl radicals that lead to the death of these beta cells [12,27,44,45]. The pancreatic beta cells are characterized by their low antioxidative defence capacity that leads to their death and the insulin-dependent alloxan diabetes [44,45].…”
Section: Discussionmentioning
confidence: 76%
“…Nowadays, therapeutic dietary nutrition and numerous plant natural products can assist the mechanisms of body homeostasis and protect or ameliorate metabolic syndrome [9]. Several herbal extracts and natural products have proved highly effective in the treatment of both diabetes and hyperlipidaemia [9][10][11][12]. In addition, Lachin and Reza [13] reported that cherries protect against alloxan-induced diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups LDE, HDE and SAD significantly reduced (p<0.05) lipid peroxidation expressed as malondialdehyde levels, thus reversing the cellular damage caused by oxidative stress. The efficacy of Diodia sarmentosa is similar to that of Salvadora persica in the reduction of lipid peroxidation (MDA activity) [35].…”
Section: Results Of In Vivo Antioxidant Activitiesmentioning
confidence: 87%
“…This increase in the antioxidant enzyme superoxide dismutase, reduced superoxide radicals by the dismutation of superoxide radical to form hydrogen peroxide and oxygen. The efficacy of Diodia sarmentosa in the increase of SOD activity can be likened to the efficacy of Salvadora persica in the increase of Superoxide dismutase activity in alloxan induced diabetic rats [35].…”
Section: Results Of In Vivo Antioxidant Activitiesmentioning
confidence: 99%